(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Individuals are naturally said to have hegemonic control and freedom over what to do with their skin and body, including what products to apply for aesthetic purposes. Today, individuals no longer have full monopoly over what to do with their skin. How and why does the state find interest in the treatment people give to their skin and, in particular, attempt to change skin colour using cosmetic products? What are the implications of state penetration in people’s skin? The paper analyses a case of the Cameroon government’s decision to ban the importation and use of cosmetic products in Cameroon. On 19 August 2022, Cameroon’s Minister of Public Health signed and made public ministerial Decision No. 193/MINSANTE of 19 August 2022, banning the importation, production and distribution of cosmetic and corporal hygiene products that contain skin bleaching substances. The results indicate that while government concern for how people treat their skin could be regarded as an extension of public health policy, it is not always welcomed by a pro-skin bleaching public who sees in the decision a government attempt to control and influence people’s corporal attitude and behaviour. This could also mean a violation of their right to the kind of skin colour they wish to have. State-government penetration in the skin reflects an extension of public policy towards health and a political attempt to limit people’s corporal attitude and behaviour. The government intervenes by issuing bans on products used to change skin colour, usually from ‘black to white’. The government penetrates the skin through public policy, which fundamentally involves governmental decisions to control what product should or should not be applied to the skin. This in turn limits the freedom and hegemony individuals enjoy over their body and skin.